2017
DOI: 10.1016/j.rmcr.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with riociquat and inhaled treprostinil in inoperable and progressive chronic thromboembolic pulmonary hypertension

Abstract: Chronic thromboembolic pulmonary hypertension (CTEPH) is characterized by formation of chronic, organized thrombus in pulmonary arteries resulting in development of pulmonary hypertension. We describe the favorable recovery of a patient with inoperable CTEPH treated with combination riociguat and inhaled treprostinil.The patient is a 77 year old female who presented with bilateral pulmonary emboli and was anticoagulated with warfarin for six months. One year later the patient developed recurrent dyspnea and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…The third patient experienced some general discomfort along with worsening dyspnoea and reduction in functional capacity after receiving riociguat. The safety findings in the three cases presented are consistent with a previous case study of a patient with CTEPH who transitioned from sildenafil/treprostinil to riociguat/treprostinil with no adverse effects [34] , and with clinical trial data. In the PATENT-1 and CHEST-1 clinical trials, adverse events occurring more frequently (by ≥3%) in patients receiving riociguat than in those receiving placebo were headache (27% vs 18%), dyspepsia/gastritis (21% vs 8%), dizziness (20% vs 13%), nausea (14% vs 11%), diarrhoea (12% vs 8%), hypotension (10% vs 4%), vomiting (10% vs 7%), anaemia (7% vs 2%), gastroesophageal reflux disease (5% vs 2%) and constipation (5% vs 1%) [27] , [28] , [35] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The third patient experienced some general discomfort along with worsening dyspnoea and reduction in functional capacity after receiving riociguat. The safety findings in the three cases presented are consistent with a previous case study of a patient with CTEPH who transitioned from sildenafil/treprostinil to riociguat/treprostinil with no adverse effects [34] , and with clinical trial data. In the PATENT-1 and CHEST-1 clinical trials, adverse events occurring more frequently (by ≥3%) in patients receiving riociguat than in those receiving placebo were headache (27% vs 18%), dyspepsia/gastritis (21% vs 8%), dizziness (20% vs 13%), nausea (14% vs 11%), diarrhoea (12% vs 8%), hypotension (10% vs 4%), vomiting (10% vs 7%), anaemia (7% vs 2%), gastroesophageal reflux disease (5% vs 2%) and constipation (5% vs 1%) [27] , [28] , [35] .…”
Section: Discussionsupporting
confidence: 88%
“…A recent interim analysis of data from the open-label, uncontrolled, Phase IIIb RESPITE (Riociguat Clinical Effects Studied in Patients With Insufficient Treatment Response to PDE5 Inhibitor) study suggested that switching from PDE5 inhibitors to riociguat improved a range of clinical and haemodynamic endpoints in patients with PAH who have had an inadequate response to PDE5 inhibition [33] . In addition, a recent case study described substantial improvements in exercise capacity and haemodynamics in a patient with progressive CTEPH after switching from sildenafil to riociguat while continuing inhaled treprostinil [34] . However, real-world data regarding the switching of patients with CTEPH or PAH from PDE5 inhibitors to riociguat are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, many other targeted drugs are also used to treat patients with CTEPH. One previous study reported the significant recovery of a patient with inoperable and progressive CTEPH who was treated with riociguat and inhaled treprostinil [ 27 ]. An open-label study observed significant improvements in the WHO FC, 6MWD, PVR, BNP, and 5-year survival rate, in patients with severe and inoperable CTEPH [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“… 24 In PAH, a deficiency of NO synthase in pulmonary vascular endothelial cells results in reduced NO production which affects vascular tone and other cellular activities in the vessel wall. 25 …”
Section: Methodsmentioning
confidence: 99%
“…24 In PAH, a deficiency of NO synthase in pulmonary vascular endothelial cells results in reduced NO production which affects vascular tone and other cellular activities in the vessel wall. 25 Since the 1990s, several agents targeting the NO pathway have been approved for the treatment of PAH including PDE5is (tadalafil, sildenafil) and sGC stimulators (riociguat). PDE5is are vasodilators that enhance and prolong cGMP action by selectively inhibiting the cGMP specific PDE5 isoenzyme that catalyzes the breakdown of cGMP.…”
Section: The Nitric Oxide Pathway In Pahmentioning
confidence: 99%